2012
DOI: 10.1111/j.1464-410x.2012.11333.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to early recurrence in clinically localized prostate cancer

Abstract: What's known on the subject? and What does the study add?• Currently available nomograms to predict preoperative risk of early biochemical recurrence (EBCR) after radical prostatectomy are solely based on classic clinicopathological variables. Despite providing useful predictions, these models are not perfect. Indeed, most researchers agree that nomograms can be improved by incorporating novel biomarkers. In the last few years, several single nucleotide polymorphisms (SNPs) have been associated with prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…A small study in a Turkish population could find no evidence of an association of SULT1A1 and prostate cancer risk, even when stratifying by smoking status (Arslan, 2010). A larger study found a risk of biochemical recurrence (OR 1.43, 95% CI 1.05–1.95) associated with the SULT1A1*1 allele (Borque et al, 2013) in over 700 men undergoing radical prostatectomy after five years follow-up. One of the first reports of SULT1A1 and prostate cancer risk found that Caucasians homozygous for the SULT1A1*1 high activity allele were at increased risk for prostate cancer (OR 1.68; 95% CI 1.05–2.68) but the association in African-Americans did not reach significance (OR, 1.60; 95% CI, 0.46–5.62; Nowell et al, 2004).…”
Section: Sult1a1 Genetic Variation and Prostate Cancer Riskmentioning
confidence: 98%
“…A small study in a Turkish population could find no evidence of an association of SULT1A1 and prostate cancer risk, even when stratifying by smoking status (Arslan, 2010). A larger study found a risk of biochemical recurrence (OR 1.43, 95% CI 1.05–1.95) associated with the SULT1A1*1 allele (Borque et al, 2013) in over 700 men undergoing radical prostatectomy after five years follow-up. One of the first reports of SULT1A1 and prostate cancer risk found that Caucasians homozygous for the SULT1A1*1 high activity allele were at increased risk for prostate cancer (OR 1.68; 95% CI 1.05–2.68) but the association in African-Americans did not reach significance (OR, 1.60; 95% CI, 0.46–5.62; Nowell et al, 2004).…”
Section: Sult1a1 Genetic Variation and Prostate Cancer Riskmentioning
confidence: 98%
“…Currently, regression is still commonly used for disease prediction. For example, a search of PubMed revealed 10 articles published in 2013 which applied regression methods for the prediction of a variety of diseases, including cerebrovascular disease, age-related macular degeneration, and hypertrophic cardiomyopathy (Abraham et al, 2013; Borque et al, 2013; Gruner et al, 2013; Harada et al, 2013; Mondul et al, 2013; Romano et al, 2013; Schellekens et al, 2013; Sharma et al, 2013; Tsai et al, 2013; Uddin et al, 2013). In addition, extensions including regression of the whole genome using a Best Linear Unbiased Prediction method (G-BLUP) can produce more highly predictive models (de Los Campos et al, 2013).…”
Section: Utility and Methodsmentioning
confidence: 99%
“…The prediction of biochemical recurrence (BCR) after radical prostatectomy, radiotherapy (RT), or brachytherapy is an essential issue widely analyzed in prostate cancer (PCa; [1][2][3][4][5][6]). Rising prostate-specific antigen (PSA) levels will be the result of either a local recurrence or systemic recurrence because of tumor dissemination.…”
Section: Materials Und Methodenmentioning
confidence: 99%
“…Jedes Nomogramm entspricht einer Kategorie des Gleason-Score, entweder 6, 7, oder 8-10. Alle Nomogramme wurden mittels eines einzigen proportionalen Hazard-Regressionsmodells etabliert, das auch nach Monaten der ADT (0,[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] stratifiziert wurde. Die Aussagekraft dieses Modells wurde anhand von Kalibrierung, unterschiedlicher Behandlung und klinischem Nutzen analysiert.…”
unclassified